Islamic Corporate Governance and Financial Performance in Companies Listed in JII - Ade Khadijatul Z. HRP; Rahmat Azahar Siregar; Sugianto; Iskandar Muda; Rahmat (PT Inovasi Pratama Internasional, 2022)
Corporate governance is very important for companies to have in order to improve financial performance. Where good corporate governance is good governance in running a company. This study aims to test whether Value Added Intellectual Coefficient (VAICTM) and good corporate governance with indicators of the size of the board of commissioners, independence of the board of commissioners, managerial ownership, affect financial performance using indicators ROA, ROE, EPS. The results showed that VAICTM had a positive and significant effect on ROA, ROE, and EPS. The size of the board of commissioners, managerial ownership has a positive and significant effect on ROA and ROE, while the independence of the board of commissioners has no effect on ROA and ROE. Managerial ownership has a positive and significant effect on EPS, while the size of the board of commissioners and the independence of the board of commissioners have no effect on EPS. Simultaneously or together with VAICTM, the size of the board of commissioners, the independence of the board of commissioners and managerial ownership shows the value of sig. of 0.000 (0.000 <0.05) from each model, this shows that H0 is rejected, meaning that at least one independent variable has an effect on the dependent variable. In other words, VAICTM, the size of the board of commissioners, the independence of the board of commissioners and managerial ownership have a simultaneous effect on ROA, ROE and EPS.